Biological basis of chronic mountain sickness - Monge C., Carlos (Acta Andina, 2025)
The Andes completed its ´present elevation about 18 million years ago when mammals had already expanded at sea level about 65 millon years ago. Therefore mammals are recent invaders of the Andean high altitude. Andeans are newcomers to high altitude with only thousands of year of hypoxic exposition. High altitude is a great biological challenge for animal life and chronic mountain sickness is the result of this disease at sea level, where mamals evolved their respiratory function in the hyperoxic atmosphere. Chronic mountaain sickness constitutes an excessive response of physiological mechanisms which appear in the course of acclimatization of newcomers to high altitude or in high altitude natives, which eventually lead to symptoms of intolerance to the hypoxic environment. There is total loss of hyperventilation with PaO2 of 40 Torr in high altitude native with excessive polycythemia and symptoms of chronic mountain sickness compared with 32 Torr in the younger asymptomac ones (excessive hypoventilation). About 33% of the population living in Cerro de Pasco (4340 m) older than 50 years have concentrations of hemoglobin above 21.3 g/dl. In chronic mountain sickness is observed an exaggerated increase in arterial pulmonary hypertension, enlargement of the carotid bodies in high altitude natives and a high incidence of chemodectomas.